GC–MS and ESI FT-ICR MS characterization on two type crude oils from the Dongying depression. (1st February 2023) - Zhang, Hanjing; Li, Sumei
Graphical abstract: Highlights: Characteristics of OSCs in saline lacustrine oils by (+) ESI FT-ICR MS. Novel maturity indices are established for low-maturity to mature oil. Establishment of oil-oil comparison parameters using OSCs with special structure. Abstract: Molecular-level characterization of sulfur-containing compounds has aroused much concern due to their relatively high abundance, sedimentary environment judgment and application at maturity. In this paper, saline lacustrine immature oils and freshwater lacustrine mature oils from the Dongying Depression (Bohai Bay Basin) were characterized by positive-ion electrospray ionization [(+) ESI] Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The saline lacustrine oils are dominated by C20 -DBE1, C30 -DBE1, and C40 -DBE3 which contain carbon skeletons of phytol, squalene and β-carotane respectively, denoting a genetic relationship between organosulfur compounds (OSCs) and their precursors. The precursors of C19 -C22 and C26 -C30 with DBE = 5 are derived from short-chain steranes and regular steroids, and their different contents can reflect the biological sources. The ratios of C20 /(C19 + C21 )-DBE1 -S1, C40 /(C39 + C41 )-DBE3 -S1, C30 /C10-55 -DBE1 -S1 and C27-29 /C10-55 -DBE5 -S1 are sensitive to organofacies, which are the first time used for oil-oil correlation. The novel maturity indices are based on the general process of thermally induced cyclization and aromatization of hundreds to thousands of OSCs from immature to mature oils. The high coefficient of correlations between the newly developed maturity parameters (DBE6-16 /DBE1+2+5 -S1, C35-60 /C10-35 -DBE1-17 -S1 ) with Ts/(Ts + Tm) and C29 -sterane αββ/(ααα + αββ) show that these utilities for assessing precisely the thermal maturity of lower maturity oils. The positive-ion ESI FT-ICR MS index has essential application prospects for organic input analysis, maturity evaluation, and oil-oil correlation.